Dulaglutide Noninferior to Liraglutide for Glycemic Control in Patients with T2DM - Vinall, Maria (MD Conference Express, 2014)
This article discusses the results from the Assessment of Weekly Administration of LY2189265 in Diabetes-6 [AWARD-6; NCT01624259] trial, which show that once-weekly dulaglutide provides glycemic control that is noninferior to once-daily liraglutide with a similar safety and tolerability profile.